SOSIALISASI TENTANG PENEGAKAN HUKUM TERHADAP PENIPUAN BISNIS BERKEDOKYANG MENERAPKAN SKEMA PIRAMIDA - Yusep Mulyana, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The factors that cause business fraud under the guise of a pyramid scheme in the territory of Indonesia can be categorized into 2 (two) namely internal and external factors. Internal factors that arise from the perpetrators, such as greed for profit, and the use of public ignorance. As for the external factors that arise from the victim, such as being easily influenced by persuasion, still has a practical mindset, and lacks information. Another factor is due to economic pressure. The countermeasures carried out by the police are carried out in a preventive manner by conducting press releases, outreach, and education to the public in collaboration with the Investment Alert Task Force formed by the OJK by the Regional Police and repressive efforts are carried out with investigations and investigations related to business cases under the guise of implementing a pyramid scheme.